Cataracts in a population of Bengal cats in France. (25th April 2017) - Bourguet, Aurélie; Chaudieu, Gilles; Briatta, Alice; Guyonnet, Alexandre; Abitbol, Marie; Chahory, Sabine
Abstract: Objective: To document the clinical appearance and prevalence of cataracts in a French population of Bengal cats. Methods: Two distinct populations of Bengal cats were examined as follows: (i) 51 animals recruited for evaluation of national prevalence of ocular diseases in an observational study conducted between October 2014 and November 2016 at the Alfort ophthalmology unit; (ii) 12 patients referred for cataract diagnosis examined at a veterinary eye clinic located in central France, between December 2014 and February 2016. Buccal swabs or blood samples for DNA analysis were collected from all patients. The pedigrees of the examined Bengal cats were also investigated. Results: Cataracts were diagnosed in 23 of 51 (45%) cats in the observational study and in all cats in the referral population, mostly bilaterally. Visual impairment was never reported. Age of subjects affected by cataracts ranged from 3 months to 9.6 years (median: 1.9 years). Cataracts were classified as nuclear cataracts (14 of 23 in the observational group and 12 of 12 in the referral group) with a focal, perinuclear, posterior, or complete nuclear pattern, or posterior polar subcapsular cataracts (10 of 23 only in the observational group). An inherited congenital origin appears to be the most likely hypothesis. The pedigree analysis suggests a hereditary component of cataract formation, but further analyses in a larger population or test matings are needed to determine the exact mode of inheritance. Conclusion: Presumed inherited cataracts appear to have a high prevalence in Bengal cats in France. The main manifestations are nuclear or subcapsular form, mostly bilateral, symmetrical, and apparently nonprogressive.